The base rate neglect in episodic memory. Issue 2 (7th February 2020) - Lu, Yong; Nieznański, Marek
ABSTRACT: The main objective of the present research was, for the first time, to assess a potential similarity in the representational bases for the base rate neglect in memory versus conditional probability judgment. Participants learned target and filler words, each of which was presented on a separate list (List 1 or List 2) and in a distinct colour (red or blue), with a manipulation of different base rates for these list and colour categories. During recognition tests, participants made prior and posterior episodic judgments (e.g., "What colour was the word?", "Given that the word was in red, on which list was the word?") on the target words, which respectively parallel independent and conditional probability assessments that figure in Bayes' theorem. The results implied that biased prior and posterior judgments presumably cause the base rate neglect, inasmuch as the prior cue of a low (high) base rate is likely to lead to a bias toward retrieving high (low) base rate posterior evidence. There was also a finding showing that memory analogues of probability estimates reflect the base rate neglect in both low and high base rate categories, but is presumably stronger with posterior judgment of Colour | List than List | Colour relative to the high base rate category.